A Survey of Media Resources Utilization by Lecturers in Colleges of Education, South-west Nigeria - Ogunwuyi, Babatunde Oyeyemi (Ghana Library Journal, 2022)
Media resources utilization is important for effective and efficient teaching in colleges of education in Nigeria but not all lecturers frequently utilize media resources in their teachings due to the unavailability and inaccessibility of some media resources. Many studies have examined media resource utilization by lecturers in the universities but few have researched this topic in the context of colleges of education especially those that are state-owned. Therefore, the present study investigated the frequency of media resource utilization in state-owned colleges of education in South-West Nigeria. The study is anchored on Media Richness Theory. A multi-stage procedure was adopted to select 812 lecturers for the study. Data were collected through a validated and reliable structured questionnaire with a Cronbach alpha coefficient = 0.96. Data was subjected to descriptive statistics of frequency counts, mean, percentage and standard deviation. The results reveal that textbooks, (x̅=4.45) ranked highest among the print media resources, chalk/whiteboard, ( x̅=4.01) ranked highest among the non-media resources and radio, (x̅ =3.69) was the most frequently used electronic media resource by lecturers in the colleges of education. It is recommended that the college authority should work in collaboration to make sure seminars and workshops on media resources utilization are constantly organized for lecturers to improve their skills in the use of media resources for teaching and learning.